Neo-Baroques : from Latin America to the Hollywood Blockbuster - Moser, Walter, 1942-; Ndalianis, Angela, 1960-; Krieger, Peter, 1961- (Postmodern studies ;, 2016)
The Baroque is back in contemporary culture. The ten essays authored by international scholars, and three interventions by artists, examine the return of the baroque as Neo-Baroque through interdisciplinary perspectives. Understanding the Neo-Baroque as transcultural (between different cultures) and transhistorical (between historical moments) the contributors to this volume offer diverse perspectives that suggest the slipperiness of the Neo-Baroque may best be served by the term 'Neo-Baroques'. Case studies analysed reflect this plurality and include: the productions of Belgian theatre company Abattoir Fermé; Claire Denis' French New Extremist film Trouble Every Day ; the novel Lujuria tropical by exiled El Salvadorian Quijada Urias; the science fiction blockbuster spectacles The Matrix and eXistenZ; and the spectacular grandeur of early Hollywood movie palaces and the contemporary Las Vegas Strip. Contributors: Jens Baumgarten, Marjan Colletti, Bolívar Echeverría, Rita Eder, Hugh Hazelton, Monika Kaup, Peter Krieger, Patrick Mahon, Walter Moser, Angela Ndalianis, Richard Reddaway, Karel Vanhaesebrouck, Saige Walton.